ANALISIS KESIAPAN DESA DI KECAMATAN BLAHBATUH MENUJU SMART VILLAGE - Wahyuni, Ni Wayan Dela; Paramitha, A A Istri Ita; Putra, I Gede Juliana Eka (Institut Bakti Nusantara, 2024)
Smart Village is a village development concept that encourages a village to undergo transformation with innovation and the use of technology. To accelerate the development of villages in Blahbatuh District, it is necessary to know the condition of the villages so that the government can provide appropriate policies. Therefore, measurements are needed to determine village readiness which are carried out in 7 villages with the variables smart government, smart people, smart economy, smart living, smart environment and smart mobility. The method used is the SVIM method with quantitative data processing methods and descriptive analysis. The data collection techniques used were questionnaires, interviews and observation. Based on the results of the analysis, 7 villages in Blahbatuh District have different levels of readiness in each variable. For variables that have a ready category in all villages, only smart mobility has a value above 30, while the not ready variable is in the smart environment variable with 4 villages with a readiness value below 20. Of the 7 villages studied, only Blahbatuh Village with the condition of 5 variables is said to be ready and 1 is said to be less ready.